Capital accumulation, labour market institutions, and unemployment in the medium run - Engelbert Stockhammer; Erik Klär (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
According to the mainstream view, labour market institutions (LMI) are the key determinants of unemployment in the medium run. The actual empirical explanatory power of measures for labour market institutions, however, has been called into question recently (Baker et al 2005, Baccaro and Rei 2007). The Keynesian view holds periods of high real interest rates and insufficient capital accumulation responsible for unemployment (Arestis et al 2007). Empirical work in this tradition has paid little attention to role of LMI. This paper contributes to the debate by highlighting the role of autonomous changes in capital accumulation as a macroeconomic shock. In the empirical analysis, medium-term unemployment is explained by capital accumulation, labour market institutions and a number of macroeconomic shocks in a panel analysis covering 20 OECD countries. The economic effects of institutional changes, variations in capital accumulation and other macro shocks are compared. Capital accumulation and the real interest rate are found to have statistically significant effects that are robust to the inclusion of control variables and show larger effects than LMI.
Keywords: E12; E20; E24; E60; 330; Unemployment; NAIRU; capital accumulation; labour market institutions; Keynesian economics; Arbeitslosigkeit; Natürliche Arbeitslosigkeit; Investition; Makroökonomischer Einfluss; Schock; Arbeitsmarktflexibilisierung; OECD-Staaten